The Impact of Job Promotion and Organizational Conflict on Employee Work Motivation at Bank Syariah Indonesia (BSI) Banda Aceh Branch - Azis, Abdul; Yusuf, Zulfan; Ismail (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to analyze the impact of job promotion and organizational conflict on employee work motivation at Bank Syariah Indonesia (BSI) Banda Aceh Branch. Human resources (HR) play a crucial role in achieving organizational goals. One of the factors that influence work motivation is job promotion, which is carried out fairly and transparently. Furthermore, although organizational conflict is often seen negatively, the results of this study indicate that well-managed conflict can actually improve employee motivation. The research employs a quantitative approach with multiple linear regression to examine the relationship between job promotion, organizational conflict, and work motivation. Data were collected through questionnaires distributed to 45 employees at BSI Banda Aceh Branch. The analysis results show that clear and fair job promotions positively affect employee motivation. The regression coefficient for job promotion is 0.220, indicating that a 1% increase in job promotion can raise employee motivation by 0.220%. On the other hand, well-managed organizational conflict also positively affects work motivation, with a regression coefficient of 0.178, showing that a 1% change in well-managed conflict can increase employee motivation by 0.178%. Based on these findings, it is recommended that the management of BSI Banda Aceh Branch improve job promotion policies to be more transparent and fair, and create a more effective conflict resolution system to support employee motivation and performance.